Theta Activity Dynamics during Embedded Response Plan Processing in Tourette Syndrome - Wendiggensen, Paul; Paulus, Theresa; Bluschke, Annet; Takacs, Adam; Toth-Faber, Eszter; Weissbach, Anne; Bäumer, Tobias; Frings, Christian; Roessner, Veit; Münchau, Alexander; Beste, Christian (Biomedicines, 2023)
Gilles de la Tourette syndrome (GTS) is a neuropsychiatric disorder. Because motor signs are the defining feature of GTS, addressing the neurophysiology of motor processes is central to understanding GTS. The integration of voluntary motor processes is subject to so-called “binding problems”, i.e., how different aspects of an action are integrated. This was conceptualized in the theory of event coding, in which ‘action files’ accomplish the integration of motor features. We examined the functional neuroanatomical architecture of EEG theta band activity related to action file processing in GTS patients and healthy controls. Whereas, in keeping with previous data, behavioral performance during action file processing did not differ between GTS and controls, underlying patterns of neural activity were profoundly different. Superior parietal regions (BA7) were predominantly engaged in healthy controls, but superior frontal regions (BA9, BA10) in GTS indicated that the processing of different motor feature codes was central for action file processing in healthy controls, whereas episodic processing was more relevant in GTS. The data suggests a cascade of cognitive branching in fronto-polar areas followed by episodic processing in superior frontal regions in GTS. Patients with GTS accomplish the integration of motor plans via qualitatively different neurophysiological processes.